A Review and Clinical Perspective of the Impact of Osteoporosis on the Spine. (16th July 2019) - Carlson, Bayard C.; Robinson, William A.; Wanderman, Nathan R.; Sebastian, Arjun S.; Nassr, Ahmad; Freedman, Brett A.; Anderson, Paul A.
Introduction: Osteopenia and osteoporosis are common conditions in the United States. The health consequences of low bone density can be dire, from poor surgical outcomes to increased mortality rates following a fracture. Significance: This article highlights the impact low bone density has on spine health in terms of vertebral fragility fractures and its adverse effects on elective spine surgery. It also reviews the clinical importance of bone health assessment and optimization. Results: Vertebral fractures are the most common fragility fractures with significant consequences related to patient morbidity and mortality. Additionally, a vertebral fracture is the best predictor of a subsequent fracture. These fractures constitute sentinel events in osteoporosis that require further evaluation and treatment of the patient's underlying bone disease. In addition to fractures, osteopenia and osteoporosis have deleterious effects on elective spine surgery from screw pullout to fusion rates. Adequate evaluation and treatment of a patient's underlying bone disease in these situations have been shown to improve patient outcomes. Conclusion: With an increased understanding of the prevalence of low bone mass and its consequences as well an understanding of how to identify these patients and appropriately intervene, spine surgeons can effectively decrease the rates of adverse health outcomes related to low bone mass.